Cell Proliferation, Migration, and Neurogenesis in the Adult Brain of the Pulse Type Weakly Electric Fish, Gymnotus omarorum - Olivera-Pasilio, Valentina; Lasserre, Moira; Castelló, María E. (Frontiers in Neuroscience, 2017)
Adult neurogenesis, an essential mechanism of brain plasticity, enables brain development along postnatal life, constant addition of new neurons, neuronal turnover and/or regeneration. It is amply distributed but negatively modulated during development and along evolution. Widespread cell proliferation, high neurogenic and regenerative capacities are considered characteristics of teleost brains during adulthood. These anamniotes are promising models to depict factors that modulate cell proliferation, migration and neurogenesis, and might be intervened to promote brain plasticity in mammals. Nevertheless, the migration path of derived cells to their final destination was not studied in various teleosts, including most weakly electric fish. In this group adult brain morphology is attributed to sensory specialization, involving the concerted evolution of peripheral electroreceptors and electric organs, encompassed by the evolution of neural networks involved in electrosensory information processing. In wave type gymnotids adult brain morphology is proposed to result from lifelong region specific cell proliferation and neurogenesis. Consistently, pulse type weakly electric gymnotids and mormyrids show widespread distribution of proliferation zones that persists in adulthood, but their neurogenic potential is still unknown. Here we studied the migration process and differentiation of newborn cells into the neuronal phenotype in the pulse type gymnotid Gymnotus omarorum. Pulse labeling of S-phase cells with 5-Chloro-2′-deoxyuridine thymidine followed by 1 to 180 day survivals evidenced long distance migration of newborn cells from the rostralmost telencephalic ventricle to the olfactory bulb, and between layers of all cerebellar divisions. Shorter migration appeared in the tectum opticum and torus semicircularis. In many brain regions, derived cells expressed early neuronal markers doublecortin (chase: 1 to 30 days) and HuC/HuD (chase: 7 to 180 days). Some newborn cells expressed the mature neuronal marker tyrosine hydroxylase in the subpallium (chase: 90 days) and olfactory bulb (chase: 180 days), indicating the acquisition of a mature neuronal phenotype. Long term CldU labeled newborn cells of the granular layer of the corpus cerebelli were also retrogradely labeled “in vivo”, suggesting their insertion into the neural networks. Quantitative analysis evidence the high neurogenic capacity of telencephalic, mesencephalic and rhombencephalic brain proliferation zones in G. omarorum, supporting the phylogenetic conserved feature of adult